ANALISIS PENGARUH KEPEMILIKAN MANAJERIAL, KEBIJAKAN UTANG, DAN PROFITABILITAS TERHADAP DIVIDEND PAYOUT RATIO PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PADA PERIODE 2007 SAMPAI DENGAN 2009 - Henryanto Wijaya; Sauliam Budianto (Universitas Kristen Krida Wacana, 2012)
Abstract: This reseaech aims at examining the impact of manajerial ownership, debt policy, and profitability on dividend payout ratio. The sample in this research are 31 firm those listed Company at Indonesian Stock Market from 2007 to 2009 with purposive sampling method. The data for this research is used secondary data that pooled from Indonesian Capital Market Directory an Analyzed with multiple regression. Research can be conclude that manajerial ownership, debt policy, and profitability have not significant influence to dividend payout ratio.Â Keywords: manajerial ownership, debt policy, profitability, dividend payout ratioÂ